Dictionary of Caribbean English usage - Allsopp, Richard (O.U.P OxfordGB, 1996)
Surveys a range of over 20,000 words and phrases taken from a region extending from Guyana in South America through the Anglophone Caribbean to the Bahamas and further round to Belize in Central America. Provides a supplement listing Caribbean and Spanish equivalents to Caribbean English items selected from the main work.